Nilai-Nilai Toleransi dalam Fiqih Sedekah di Indonesia : Studi terhadap Pemberian Sesaji Pasca Meletusnya Gunung Semeru - Ula, Siti Khoirotul; al-Asy’ari, M. Khoirul Hadi (Proceedings of Annual Conference for Muslim Scholars, 2022)
Recently, we were shocked by a video of a moslem youth kicking “sesaji” that placed around the mountain after the eruption of Semeru. In the video, the young man judged that the root of all natural disasters, including the eruption of Semeru, was the many “shirk” practiced which made Allah swt angry. Furthermore, this article is a fiqh research that will explain how the position of "sesaji" in the perspective of fiqh “sedekah” in Indonesia. In this article, the main object of this study is the event of giving “Sesaji” after the eruption of Semeru by the Moslems there. As a fiqh research, of course the explanation that will be explained in this article is how fiqh sedekah reads these activities which the sedekah itself is one of the teachings of Islam which has a high meaning and value of tolerance for the others. Fiqh sedekah in the context of religiousities in Indonesia is very flexible and relevant to the context of a multicultural society. Based on the data obtained from informants regarding the origin of this "sesaji", it was concluded that the sesaji were given by moslems intended to reject bala’ while avoiding the anger of the jinn. The local community considers that "sesaji" can be a means to ask permission from God Almighty so that the genie is not angry, because the genie is also a creature of God. The "sesaji" are placed around the mountain after the eruption of Semeru to be eaten by birds and other animals and are not intended for alms to humans. In the event of giving sesaji, the values ​​of tolerance towards fellow creatures of God, both to humans and other creatures, which are included in the fiqh sedekah are contained in the activity of giving sesaji after the eruption of Semeru.